Large Amplitude Oscillatory Shear (LAOS) studies of fibrin and whole blood clots - Tunde F. Lamer (2018)
Venous Thromboembolism encompasses a progression of diseases where initially a blood clot is formed in the deep veins. The clot can break off, travel in the bloodstream and lodge in the pulmonary arteries leading to a lack of blood supply to the lungs. This embolic event known as pulmonary embolism can often be fatal but is difficult to predict. This thesis investigates the nonlinear rheological properties of blood clots that are important for understanding the mechanisms of embolism. The work presented uses the advanced rheological technique, Large Amplitude Oscillatory Shear (LAOS) in both strain-controlled (LAOStrain) and stress-controlled (LAOStress) modes in order to characterise the nonlinear viscoelastic properties of fibrin and whole blood clots. Furthermore, the role of clot microstructure in the nonlinear viscoelastic properties of the mature clot was investigated. Alternating application of LAOS and Small Amplitude Oscillatory Shear (SAOS) provided detailed information of reversible and irreversible structural changes of the fibrin network revealing several distinct regions of nonlinear viscoelastic behaviour up to the point of network fracture. Shifting of these regions to different levels of stress was seen in fibrin and whole blood clots formed with different microstructures as manipulated by the addition of thrombin or heparin. Of significance, the rheologically derived value of fractal dimension, obtained from the measurement of a Gel Point using SAOS, correlated with the eventual fracture stress in a LAOStress measurement. This work suggests that incipient clot microstructure influences the ability of the fully formed clot to resist fracture as a consequence of haemodynamic forces encountered in blood vessels and sheds light on the mechanisms of changes in the conformation of the fibrin network up to the point of fracture. A main conclusion of this thesis is that the measurement of a fractal dimension of a blood clot may serve as a much needed biomarker for predicting embolism in patients whom experience thrombosis.